Inflammasome Adaptor ASC Is Highly Elevated in Lung Over Plasma and Relates to Inflammation and Lung Diffusion in the Absence of Speck Formation - Gavrilin, Mikhail A.; McAndrew, Christian C.; Prather, Evan R.; Tsai, MuChun; Spitzer, Carleen R.; Song, Min-Ae; Mitra, Srabani; Sarkar, Anasuya; Shields, Peter G.; Diaz, Philip T.; Wewers, Mark D. (Frontiers in Immunology, 2020)
Rationale: Caspase-1 is a zymogen whose activation depends the assembly of ASC monomers into insoluble prion-like polymers (specks). ASC polymers support caspase-1 dimer formation inducing a proximity mediated auto-activation of caspase-1. Therefore, the amount and nature of ASC monomers and polymers in lung bronchoalveolar lavage fluid (BALF) might serve as a marker of lung inflammasome activity. Objectives: To determine whether lung ASC concentrations or oligomerization status predicts lung function or activity of lung inflammation. Methods: BALF ASC amount and oligomerization status was studied in three distinct cohorts: 1) young healthy nonsmokers, vapers and smokers; 2) healthy HIV+ smokers who underwent detailed lung function studies; and 3) hospitalized patients with suspected pneumonia. We quantified cell free BALF ASC levels by ELISA and immunoblot. Oligomers (i.e. ASC specks) were identified by chemical crosslinking and ability to sediment with centrifugation. Measurement and Main Results: ASC levels are significantly higher in lung lining fluid than in plasma as well as higher in smoker lungs compared to nonsmoker lungs. In this context, ASC levels correlate with macrophage numbers, smoking intensity and loss of lung diffusion capacity in a well characterized cohort of healthy HIV+ smokers. However, only monomeric ASC was found in our BALF samples from all subjects, including patients with lung infections. Conclusions: Even though, most, if not all, extracellular ASC in BALF exists in the soluble, monomeric form, monomeric ASC concentrations still reflect the inflammatory status of the lung microenvironment and correlate with loss of lung function.